2016
DOI: 10.21884/ijmter.2016.3065.thkr0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spoiler Design on Hatchback Car

Abstract: The aerodynamic aspects of automobiles have received more interest recently. Detailed knowledge of vehicle aerodynamics is more important to improve fuel efficiency and enhance stability of vehicle at high speed cruising. Additionally it provides improved external aesthetics. There are different ways to improve the aerodynamic performance of a car like using spoilers, air dam, diffuser etc. This paper deals with effect of addition of spoiler on Volkswagen Polo car in terms of coefficient of drag and lift. Main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Based on an analysis of a vehicle with and without a spoiler, it was found that spoilers have a significant effect on the performance of a hatchback. As a result of the analysis, the drag coefficient increased by 8.33% with the addition of the spoiler and the lift coefficient decreased by 59.09% with the addition of the spoiler [5]. Improving the aerodynamic performance of the wing section is achieved by increasing the lift force generated around the wing section and reducing the drag force.…”
mentioning
confidence: 93%
“…Based on an analysis of a vehicle with and without a spoiler, it was found that spoilers have a significant effect on the performance of a hatchback. As a result of the analysis, the drag coefficient increased by 8.33% with the addition of the spoiler and the lift coefficient decreased by 59.09% with the addition of the spoiler [5]. Improving the aerodynamic performance of the wing section is achieved by increasing the lift force generated around the wing section and reducing the drag force.…”
mentioning
confidence: 93%